The Misattributed and Silent Causes of Poor COVID-19 Outcomes Among Pregnant Women - Machluf, Yossy; Rosenfeld, Sherman; Ben Shlomo, Izhar; Chaiter, Yoram; Dekel, Yaron (Frontiers in Medicine, 2021)
Abundant evidence strongly suggests that the condition of pregnancy makes women and their fetuses highly vulnerable to severe Corona-virus 2019 (COVID-19) complications. Here, two novel hypoxia-related conditions are proposed to play a pivotal role in better understanding the relationship between COVID-19, pregnancy and poor health outcomes. The first condition, “misattributed dyspnea (shortness of breath)” refers to respiratory symptoms common to both advanced pregnancy and COVID-19, which are mistakenly perceived as related to the former rather than to the latter; as a result, pregnant women with this condition receive no medical attention until the disease is in an advanced stage. The second condition, “silent hypoxia”, refers to abnormally low blood oxygen saturation levels in COVID-19 patients, which occur in the absence of typical respiratory distress symptoms, such as dyspnea, thereby also leading to delayed diagnosis and treatment. The delay in diagnosis and referral to treatment, due to either “misattributed dypsnea” or “silent hypoxia”, may lead to rapid deterioration and poor health outcome to both the mothers and their fetuses. This is particularly valid among women during advanced stages of pregnancy as the altered respiratory features make the consequences of the disease more challenging to cope with. Studies have demonstrated the importance of monitoring blood oxygen saturation by pulse oximetry as a reliable predictor of disease severity and outcome among COVID-19 patients. We propose the use of home pulse oximetry during pregnancy as a diagnostic measure that, together with proper medical guidance, may allow early diagnosis of hypoxia and better health outcomes.